Pemanfaatan Digital Marketing Shopee dan Shopee Live sebagai Optimalisasi Pemasaran Fashion Muslimah “Gamaleea” dalam Menaikkan Omset Penjualan UMKM - Putri, Synthia Sumartini; Almini, Almini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The use of digital marketing is currently being greatly utilized by micro, small and medium enterprises (MSMEs). What micro, small and medium businesses use is Shopee Live or Shopee. With Shopee, it helps people meet household needs. Like the micro, small and medium Muslim fashion business